Greedy method for solving the Langkawi tourist route: A case study - Hashim, Zakiah; Mat Desa, Wan Laailatul Hanim; Aziz, Hurul Ain; Mohd Zaki, Nur Mariana Zaimah (UUM College of Business, 2018)
This paper presents a real case study to determine the optimal tourist route at Langkawi Island. The Langkawi Island was selected as the case study because normally, tourist travel to this island will drive the rented car as the primary mode of transport.Thus, the aim of this paper is to develop a mathematical model to find an optimal route for tourist to travel to their interesting places around Langkawi Island.In order to solve the problem, Greedy method was applied in this study and MATLAB version 7.8 has been used to get the solution.The result obtained shows that Nearest Greedy Insertion method gives better result compared to the Nearest Greedy method. The minimum value of the route selection gives effect to the cost of travelling.Therefore, from this study, the best route that connect from one interesting place to others place can be suggested to the tourist as a guidance.In addition, tourist can save their time and money to visit all interesting places in this study.